2023
DOI: 10.1111/1468-0009.12623
|View full text |Cite
|
Sign up to set email alerts
|

Child Poverty and Health: The Role of Income Support Policies

Abstract: r Child poverty is associated with both short-and long-term health and well-being, and income support policies can be used to improve child health.r This article reviews the types of income support policies used in the United States and the evidence of the effectiveness of these policies in improving child health, highlighting areas for future research and policy considerations specific to income support policies. C hild poverty is associated with both short-and long-term health and well-being. 1,2 Poverty aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 91 publications
(147 reference statements)
0
6
0
Order By: Relevance
“…In this issue, Pilkauskas goes into further detail about how income support can serve as a policy solution to address upstream health challenges. 26 Research also reveals that intensive, high-quality early childhood intervention programs can have large, positive, long-term, educational, and physical and mental health impacts on children from disadvantaged backgrounds. The Perry Preschool Program was a 2-year intervention in which Black children ages 3 to 4 years, living in poverty, were randomized to participate in a preschool program or to be in a control group.…”
Section: Public Policy Reforms Focused On the Well-being Of Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Pilkauskas goes into further detail about how income support can serve as a policy solution to address upstream health challenges. 26 Research also reveals that intensive, high-quality early childhood intervention programs can have large, positive, long-term, educational, and physical and mental health impacts on children from disadvantaged backgrounds. The Perry Preschool Program was a 2-year intervention in which Black children ages 3 to 4 years, living in poverty, were randomized to participate in a preschool program or to be in a control group.…”
Section: Public Policy Reforms Focused On the Well-being Of Childrenmentioning
confidence: 99%
“…President Biden's Infrastructure Investment and Jobs Act (2021) and Inflation Reduction Act (2022) have the potential to contribute greatly to addressing the well‐being of children. In this issue, Pilkauskas goes into further detail about how income support can serve as a policy solution to address upstream health challenges 26 …”
Section: Public Policy Reforms Focused On the Well‐being Of Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…We also performed sensitivity analyses where we changed the observation window of our study. First, we excluded the first month of the CTC payment, given evidence that families were somewhat less likely to have received the credit in the first month after implementation of the reforms ( Pilkauskas & Cooney, 2021 ; Michelmore & Pilkauskas, forthcoming ), and results were robust to that exclusion. Second, we excluded the last month of the observation window in case families responded differently as monthly payments were ending.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence increasingly suggests that income supports have an impact on pregnancy and child health outcomes. 60 Comprehensive evidence from low-and middleincome countries suggests that cash transfers lower mortality for women and children younger than 5 years of age. 61 Quasi-experimental studies of the Earned Income Tax Credit have shown improvements in birth outcomes when income support amounts increased.…”
Section: Direct Cash Transfers: Consistent With Health System Values ...mentioning
confidence: 99%